1995
DOI: 10.1111/j.1365-2621.1995.tb06288.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase and Lipoxygenase Influence on Stability of Polyunsaturated Fatty Acids in Sweet Corn (Zea mays L.) during Frozen Storage

Abstract: The effect of blanching treatments and packaging materials on lipoxygenase (LOX) and peroxidase (POD) activity and fatty acid stability of two cultivars of sweet corn (Jubilee and GH-2684) were evaluated during 9 mo storage at -20°C. Complete inactivation of LOX and POD was obtained with 9 and 15 min of steam blanching, respectively. Relative fatty acid content revealed no change in fatty acid composition during storage. Control of degradation of polyunsaturated fatty acids (PUFA) did not depend on oxygen perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
(13 reference statements)
1
18
1
1
Order By: Relevance
“…The phenomena of POD regeneration has been confused by POD recoveries following freezing. Unblanched frozen corn did not show an increase in the POD isoform activity following freezing at -20 °C in this study and (31). Blanched asparagus showed regeneration after 1.5 months storage at -18 °C; but unblanched asparagus also increased POD activity to > 200% of the original activity (29).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The phenomena of POD regeneration has been confused by POD recoveries following freezing. Unblanched frozen corn did not show an increase in the POD isoform activity following freezing at -20 °C in this study and (31). Blanched asparagus showed regeneration after 1.5 months storage at -18 °C; but unblanched asparagus also increased POD activity to > 200% of the original activity (29).…”
Section: Discussioncontrasting
confidence: 55%
“…Lipoxygenase, normally a more heat labile enzyme than POD, had a greater heat stability than soluble POD in asparagus (40). A recent study on the breakdown of polyunsaturated fatty acids revealed that the percentage composition of linoleic acid did not change in unblanched and blanched sweet corn, suggesting that enzyme-controlled breakdown (lipoxygenase, LOX) did not occur during frozen storage (31). However, when LOX and POD were added to blanched corn homogenates, only the added LOX homogenate reproduced the combination odour of unblanched corn (41).…”
Section: Discussionmentioning
confidence: 94%
“…Lipoxygenases, which catalyze the oxygenation of polyunsaturated fatty acids, are key enzymes in this pathway and their presence is believed to be the chief reason for the need for blanching prior to frozen storage. Some authors stated that a complete inactivation of lipoxygenase (LOX) and peroxidase (POD) from sweet corn can be achieved within 9 and 15 min of steam blanching, protecting the PUFAs from degradation (Rodriguez-Saona et al 1995;Dornenburg and Davies 1999). On the contrary, blanching of raw meat led to a decrease in PUFAs content, higher free fatty acid levels and significantly higher peroxide values (Fox et al 1994).…”
Section: Blanchingmentioning
confidence: 97%
“…The fatty acid composition of the oils was determined using a fatty acid methyl ester (FAME) procedure [25]. Esterification was achieved by adding 10 mL of 4% methanolic-sulfuric acid to 0.5 g oil sample plus 1 mL benzene in a glass test tube with a Teflon screw top cap.…”
Section: Fatty Acid Analysismentioning
confidence: 99%